THE EFFECT OF RED ONION TO DECREASE BLOOD SUGAR LEVELS IN CLIENTS WITH HYPERGLYCEMIA - Tendean, Angelia , Friska; Imato, Octaviany Yemima; Walewangko, Acnes Walewangko Bela (11th International Scholars Conference, 2016)
The red onion (Allium cepa.Linn) has long been used in herbal medicine and commonly used as flavoring agent cookery. Red onion has many benefits for health to decrease cholesterol, anticoagulant and antioxidant and decrease blood sugar. The aim of present study was to know the effect of red onion to decrease blood sugar levels in clients with hyperglycemia and also to identification the effect of red onion to decrease blood sugar levels, if connected by factor of age and gender in clients with hyperglycemia. In this study used quasi experiment with pretest-posttest with therapy group and control group involving clients with hyperglycemia as many as 50 respondents of therapy group and 50 respondents of control group in sub district Kalawat. The result of this study was using t-test independent showed that there was decrease blood sugar levels after consumption red onion juice for 1 day at significance value ρ =0,00<0,05, no change if connected by factor of age at significance value ρ=0,488>0,05 and factor of gender at significance value ρ=0,942>0,05. Conclusion, the red onion had effect to decrease blood sugar in client with type II diabetes mellitus in sub district Kalawat. Suggestion, people can use red onion as one of herbal medicine to decrease blood sugar levels.